2009
DOI: 10.5007/2177-5230.2009v24n48p103
|View full text |Cite
|
Sign up to set email alerts
|

A Estrada de Ferro São Paulo-Rio Grande na formação econômica regional em Santa Catarina

Abstract: ResumoO objetivo deste artigo é analisar e discutir a construção e a expansão da Estrada de Ferro São Paulo-Rio Grande (EFSPRG) no Brasil meridional, com ênfase nos trechos do território catarinense no meio oeste e planalto norte. O texto está dividido em três tópicos. Inicialmente será feita uma breve introdução que apresenta os motivos da expansão ferroviária no Brasil meridional. Em seguida, será analisada a construção do trecho catarinense dentro do complexo ervateiro e madeireiro, destacando o trecho entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
3
0
3
Order By: Relevance
“…Almost all forest remnants are secondary forest, with a history of unplanned logging and land use change in favour of agriculture and pasture. The timber exploration started at the beginning of the 20th century with the construction of railroads crossing Santa Catarina from north to south and to the Atlantic Ocean, which was accompanied by land concession to forest exploration and colonization (Goularti Filho, 2009). With the rapid colonization and multiplication of roads and highways, forests continued to give way to agriculture in the flatter areas during the first half of the 20th century.…”
Section: Study Sitementioning
confidence: 99%
“…Almost all forest remnants are secondary forest, with a history of unplanned logging and land use change in favour of agriculture and pasture. The timber exploration started at the beginning of the 20th century with the construction of railroads crossing Santa Catarina from north to south and to the Atlantic Ocean, which was accompanied by land concession to forest exploration and colonization (Goularti Filho, 2009). With the rapid colonization and multiplication of roads and highways, forests continued to give way to agriculture in the flatter areas during the first half of the 20th century.…”
Section: Study Sitementioning
confidence: 99%
“…Because of its large latitudinal range and heterogeneous environmental condition, the Atlantic Forests shelter an enormous biodiversity (Carnaval et al 2009;Oliveira et al 2019a), despite being mostly composed of secondary degraded forests . The forest in the study region is primarily found in small fragments of less than 50 ha surrounded by an agricultural matrix (Vibrans et al 2013;Schaadt & Vibrans 2015), traversed by a vast road network (Goularti Filho 2009). Old-growth stands in Atlantic Forests can stock similar densities of carbon to Amazon forests (see de Paula et al, 2011;Pan et al, 2011;Pyles et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…ligada ao contexto de integração ferroviária do sul do Brasil, especialmente em virtude de demandas econômicas, militares, demográficas e territoriais. Nesse âmbito, entre as décadas de 1930 e 1960, a malha configurou-se como um grande corredor de transporte de madeira e cereais do meio oeste e planalto norte de Santa Catarina, com significativa parte dessa carga oriunda do Paraná (GOULARTI FILHO, 2009 Historicamente, a estação ferroviária e sua respectiva linha férrea tiveram importância considerável para as empresas de Joinville, sobretudo até a década de 1960, período em que ocorreram forte crescimento urbano e acelerada industrialização da cidade. De acordo com o historiador Apolinário Ternes (1984, p. 213), "a estrada de ferro desempenharia papel preponderante no desenvolvimento industrial desta região catarinense", especialmente para a facilitação do transporte e da circulação de grandes volumes de mercadorias fabricadas em Joinville e seus municípios circunvizinhos.…”
Section: Introductionunclassified